2012
DOI: 10.1177/1350508412459996
|View full text |Cite
|
Sign up to set email alerts
|

Barefoot entrepreneurs

Abstract: This paper makes a contribution to critical entrepreneurship studies through exploring 'barefoot’ entrepreneur[ing], i.e., the entrepreneurial practices and narratives of individuals who live primarily in marginal, poor and excluded places and contexts. Drawing on Max-Neef’s barefoot economics and a methodology based on the authoring and sharing of microstorias, the article asks how agents in deprived areas of Chile, Argentina, Zimbabwe and Ghana undertake entrepreneur[ing] from the margins or ‘periphery’. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 73 publications
(64 reference statements)
0
67
0
2
Order By: Relevance
“…Their daily entrepreneuring is very much about becoming, and becoming is always a co-production between the entrepreneur, the other, and their historical and cultural contexts (Anderson et al, 2012). This resonates with critical entrepreneurship research that examines entrepreneurship as accomplished in and through actions in local contexts (Down & Warren, 2008), as well as with recent studies that have shown how dominant understandings of entrepreneurship are challenged through explorations of creative entrepreneuring in peripheral local positions (Imas, Wilson, & Weston, 2012). Our research acknowledges the creative power of entrepreneurship to 'create sociality in local settings', thereby enabling alternative ways of being in the world (Verduijn, Dey, Tedmanson & Essers, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…Their daily entrepreneuring is very much about becoming, and becoming is always a co-production between the entrepreneur, the other, and their historical and cultural contexts (Anderson et al, 2012). This resonates with critical entrepreneurship research that examines entrepreneurship as accomplished in and through actions in local contexts (Down & Warren, 2008), as well as with recent studies that have shown how dominant understandings of entrepreneurship are challenged through explorations of creative entrepreneuring in peripheral local positions (Imas, Wilson, & Weston, 2012). Our research acknowledges the creative power of entrepreneurship to 'create sociality in local settings', thereby enabling alternative ways of being in the world (Verduijn, Dey, Tedmanson & Essers, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…The foregoing conceptual notions are pertinent to the study of economic development amongst Indigenous groups, (Imas, Wilson & Weston, 2012;Peredo & Anderson, 2006) and can present unique managerial challenges for MNCs that seek to interact with Indigenous people. In Western Australia (WA), firms in the mining industry have taken an active role in engaging Indigenous owned companies and in doing so have implemented strategies which can be viewed as a reaction to their perceived CSR.…”
Section: The Case Of the Western Australia Mining Sectormentioning
confidence: 99%
“…We wished to generate an empathetic understanding in readers unlikely to be familiar with groups like the MAC (Brunwick & Coghlan, 2007;Cunliffe, 2010;Watson, 2012) and to challenge dominant understandings through contact with the other (see Barnard, 2011;Glass, 2012;Morris, 2012;Rimmer, 2010, for example), enabling marginalised voices to be heard (Imas, Wilson, & Weston, 2012), and remedying a 'apolitical reading of organizing' (Ybema, Yanow, Vels, & Kamsteeg, 2009, p.7).…”
Section: Methodsmentioning
confidence: 99%